Evaluación médica prenupcial de enfermedades infecto contagioso y de transmisión sexual - Segovia Mera, Diana Carolina (2015)
This research called Prenuptial Medical Evaluation Disease, Contagious Infecto, the following research question was posed: How the no prenuptial medical evaluation of diseases of civil marriage prior to sexual transmission, can affect the spread of the disease newborn ?. Legal research is divided into six chapters: It will address the analysis of the problem and the effect it was necessary to hypothesize the investigation, that the solution to the problem was in compliance with the research hypothesis. It is referring to Theoretical Framework in aspects: historical, case law and legal doctrine. The methodology used in the investigation at issue described; the methods used, the types of research, people, samples of techniques and instruments used in data collection. Hypothesis through the research results obtained through interviews with officials based in Quevedo, and surveys of lawyers in free practice, they know the importance of prenuptial medical tests to ensure and protect the fundamental basis of society is the family. Conclusions and Recommendations on the settlement of disputes of a legal nature that can be solved. Finally, in the proposal, objectives, beneficiaries and social impact is described.